Phosphorylation of the PII protein (glnB gene product) in the cyanobacterium Synechococcus sp. strain PCC 7942: analysis of in vitro kinase activity. - Forchhammer, K (1995)
The PII protein in the cyanobacterium Synechococcus sp. strain PCC 7942 signals the cellular state of nitrogen assimilation relative to CO2 fixation by being phosphorylated at a seryl residue. In this study, we first determined the location of the phosphorylated seryl residue within the PII amino acid sequence. The phosphorylation site exhibits an RXS motif, a recognition sequence characteristic for cyclic AMP-dependent protein serine kinases from eukaryotes. We established an in vitro PII phosphorylation assay to further analyze the PII kinase activity in Synechococcus sp. strain PCC 7942. ATP was used specifically as a phosphoryl donor, and the PII kinase activity was shown to be stimulated by alpha-ketoglutarate. Unlike the PII-modifying uridylyltransferase- and uridylyl-removing enzyme characterized in proteobacteria, the activity of the PII kinase from the cyanobacterium did not respond to glutamine.